Iqra' in Surah Al-'Alaq: Foundation of Islamic Education and Its Relevance in Modern Learning - Alifya Zahra Tsabita; Aisyah Latika Fatmawati; Anisa Dwi Aprilia (Universitas Muhammadiyah Surakarta, 2025)
This study explores the relevance of the Iqra' principle in Surah Al-'Alaq and its integration into modern educational frameworks. Iqra', which encompasses intellectual, spiritual, and ethical dimensions, is interpreted beyond mere reading, encouraging reflection, observation, and a deeper understanding of the world. The research analyzes how these principles can contribute to the development of holistic educational approaches in the 21st century, emphasizing critical thinking, collaboration, and adaptability. The study finds that Iqra' aligns well with modern educational methods, such as project- based learning and blended learning, which promote active engagement and independent research. The integration of technology into these methodologies is discussed, highlighting the challenges of digital literacy and the need for ethical values in education. The findings suggest that Iqra' can serve as a foundation for a more ethical, value-based approach to education, addressing both cognitive and moral development. The research also emphasizes the need for future studies to explore practical models for implementing Iqra' in contemporary learning environments and to assess its long-term impact on character development and academic success. Overall, this work contributes to bridging Islamic values with modern educational demands, advocating for an education system that fosters intellectual growth while promoting ethical responsibility.